Impact of the Si/Al ratio on the ethanol/water coadsorption on MFI zeolites revealed using original quantitative IR approaches. Issue 16 (11th April 2023) - Douaihy, Rita Zakhia; Lakiss, Louwanda; El-Roz, Mohamad; Levaque, Yoann; Vimont, Alexandre; Bazin, Philippe
Abstract : The use of advanced infrared vibrational spectroscopic tools (high-throughput and gravimetric-IR coupled cells) allows obtaining quantitative data for ethanol and water adsorption and coadsorption on MFI zeolites with different Si/Al ratios. Abstract : Advanced IR vibrational spectroscopic techniques, e.g., using a coupled gravimetric-IR surface analyzer (AGIR) and a high-throughput in situ IR cell (Carroucell), have been used for the quantitative studies of the adsorption and coadsorption of ethanol and water on MFI zeolites with different Si/Al ratios. The AGIR coupling is a powerful tool for the accurate determination of the molar adsorption coefficients during coadsorption experiments since their evaluation is based on the measurement of the exact amount of adsorbed species. The use of the Carroucell set up allows characterizing all the samples simultaneously, strictly in the same gaseous and temperature environment. The molar absorption coefficients of pure adsorbed ethanol and water are determined: their values are constant whatever the Si/Al ratio of the MFI zeolites. Moreover, these coefficients are found to be identical in the case of the water–ethanol coadsorption experiments. Their use allows obtaining the exact quantity of each adsorbate specie in the binary system. At low partial pressures, the unary water adsorption experiments suggest that the amount of adsorbed water results mainly from the preferential adsorption on Brønsted acid sites in tetrameric clusters. In contrast, the adsorption of EtOH occurs on both silanol groups and Brønsted acid sites (BASs). The effect of the Si/Al ratio is only observed at relatively low partial pressures. The effect of the Si/Al ratio on the ethanol adsorption capacity is also investigated. This study directs the choice of an appropriate zeolite once it is used in membranes for drying ethanol.